Endoscopic management of retrosternal goitres through cervical approach: a single centre experience - Puntambekar, Shailesh; Bhaumik, Abhishek; Bharambe, Suyog; Chitale, Mihir; Sathe, Ravindra; Panse, Mangesh; Manerikar, Kshitij; Langade, Yogesh; Attar, M. Azharuddin Azim; Gandhi, Nikesh; Bhat, Apoorv; Ghuge, Ashutosh; et al. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Retrosternal extension of thyroid poses a significant challenge due to its size and high vascularity. The objective of this study was to assess the outcomes of endoscopic approach via cervical approach for retrosternal thyroid removal. Methods: This was a hospital based retrospective cross-sectional study, conducted among 12 patients of goitres with retrosternal extension who fulfilled the inclusion criteria for endoscopic excision via cervical approach from January 2016 to December 2020. The data was collected using patient record sheet. STATA 15.0 was used to analyse the data. Results: The median age of the participants was 62 (18.5) years. Approximately 66.7% (N=8) and 33.3% (N=4) of the patient’s respectively presented with the complaint of unilateral and bilateral swelling in the neck. The majority of the patients reported due to cosmetic reasons (58.3%), breathlessness (33.3%), hoarseness and dysphagia (8.3%). Among the patients all were euthyroid. There was no incidence of haemorrhage, tracheal and esophageal injury in the patients intraoperatively. Postoperative histopathology showed benign multinodular goiter (41.7%) and colloid formation (58.3%). Conclusions: The traditional thyroidectomy is widely accepted by the surgeons for retrosternal goitres however the results of our study suggest that the endoscopic technique is minimally invasive and safe procedure that offers excellent cosmetic satisfaction. With the careful selection of cases and surgeon expertise endoscopic thyroidectomy can yield results similar with the traditional approach however, with less complication rates and morbidity.